Amyloid A gene family expression in different mouse tissues (The Rockefeller University Press, 1986)
Serum amyloid A (SAA) is a major acute-phase reactant and apoprotein of high density lipoprotein (HDL). SAA is encoded by a family of three active genes. We examined hepatic expression and searched for extrahepatic expression of the three SAA mRNAs after injection with casein or LPS. Studies using an SAA cDNA, which detects all three SAA mRNAs, revealed that after casein injection liver SAA mRNA was elevated approximately 1,000-fold. Adrenal gland expressed SAA mRNA at a low level (0.5% of hepatic level), and was the only extrahepatic tissue with elevated SAA mRNA after casein injection. The small intestine, primarily the ileum, and the large intestine of unstimulated control animals contained 5- and 15-fold higher SAA mRNA levels than control liver. LPS also elevated liver SAA mRNA approximately 1,000-fold. However, in contrast to casein injection, every extrahepatic tissue examined expressed SAA mRNA. Lung and kidney contained 2-5% and large intestine contained nearly 10% of SAA mRNA levels found in liver RNA. SAA mRNA levels were lower in the remaining tissues and ranged from 0.1% in the brain and pancreas to 1.0% in the small intestine, with the ileum containing 50-fold more than the duodenum. Analysis of liver with SAA1, SAA2, and SAA3 mRNA-specific oligonucleotide probes revealed that SAA1 and SAA2 mRNA were elevated approximately 50-fold higher than SAA3 mRNA after casein administration. LPS, however, induced all three SAA mRNAs equally. In extrahepatic tissues, SAA1, SAA2, and SAA3 mRNAs were expressed differentially and can be grouped into three general classes: tissues expressing all three genes, tissues expressing SAA1 and SAA3, and tissues expressing predominantly or only SAA3.